Comparing the Effectiveness of Cognitive-Behavioral Therapy and Emotion-Focused Therapy on Quality of Life Components in Patients with Cervical Cancer - Norouzi , Elham; Sobhani , Ahmad; Nikyar , Hamid Reza; Rezaie Jamalouei , Hasan (KMAN Counseling & Psychology Nexus, 2025)
This study aimed to compare the effectiveness of Cognitive-Behavioral Therapy (CBT) and Emotion-Focused Therapy (EFT) in improving quality of life in women with cervical cancer. A quasi-experimental design with a pretest-posttest structure and control group was employed. Seventy-five women with cervical cancer were purposively sampled and randomly assigned to three groups: CBT, EFT, and control (25 participants each). Both interventions consisted of 12 weekly group sessions. The quality of life was measured using the WHOQOL-BREF questionnaire across physical, psychological, social, and environmental domains. Data were analyzed using mixed-design ANOVA to evaluate the effects of the interventions over time and between groups. Bonferroni post-hoc tests were conducted to identify specific differences. The mixed-design ANOVA revealed significant main effects of test stages (F = 588.22, p < 0.001, η² = 0.91) and group membership (F = 69.55, p < 0.001, η² = 0.70), as well as significant interactions between test stages and groups (F = 168.24, p < 0.001, η² = 0.86) for the total quality of life score. Bonferroni post-hoc comparisons indicated that both CBT and EFT groups significantly outperformed the control group in all quality of life domains (p < 0.001). No significant differences were found between CBT and EFT (p > 0.05), and improvements were sustained at follow-up. Both CBT and EFT are effective in improving quality of life in women with cervical cancer, with comparable outcomes. These findings highlight the value of integrating psychological therapies into cancer care programs to address the multidimensional impacts of the disease and enhance patients’ overall well-being.